PRODUCTION AND PURIFICATION OF PHARMACEUTICALLY IMPORTANT FIBRINOLYTIC ENZYME FROM BACILLUS SPECIES (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The medicinal and pharmaceutical importance of currently available thrombolytic agents like urokinase, t-PA, streptokinase, staphylokinase and others, demonstrated repeatedly since 1970s, however sometimes they cause undesirable side effects like bleeding and allergic responds. The present findings reports isolation, screening and identification of soil bacterium for production of fibrinolytic enzyme. Samples for the study were collected from different locations were first screened for proteolytic activity using skimmed milk agar plate and lastly fibrin plate method was used to evaluate fibrinolytic activity. The strain capable of producing fibrinolytic protein was identified as Bacillus Spp. Using both Bergery’s manual of systemic bacteriology and biochemical characterization simultaneously. Selected strain was than subjected to the process of fermentation using basal media for 5 days, 37°C and at 180rpm. Protein content and fibrinolytic activity were measured by Biuret method using bovine serum albumin as standard and fibrinolytic assay respectively. Three stage purification was done, that includes salting out with ammonium sulphate, followed by gel filtration chromatography and finally separated by RP-HPLC, proteins were eluted in peaks with a retention time of 2.092, 3.188, 5.178, 7.295, and 11.32 minutes. The fraction with retention time 7.295 minutes shows a maximum activity. The enzyme found to be having an optimum pH between 7.0 and 7.5. Enzyme is also stable at the optimum pH and found to lose its activity on higher side of acidity or alkalinity. It is more active at 40°C and is stable at 37°C to 43°C with slight modification in activity.